The Effect Of Combined 650 Nm And Infrared Laser On Chronic Diabetic Foot Ulcer Surface Area: A Randomized Controlled Trial (Journal of Pharmaceutical Negative Results, 2023)
Background Photobiomodulation PBM therapy reduces inflammation and oxidative stress, and accelerates cell migration and proliferation, release of key growth factors, thereby improving tissue regeneration and accelerating wound healing. Objective to investigate the effect of combined 650 nm and infrared laser on chronic diabetic foot ulcer healing. Methods Forty-five patients with an age range from 18-60 years old, both sexes, were assigned randomly into three equal groups, each group consisting of 15 patients, group A received laser therapy in sequential mode, group B received laser therapy in separate mode and the control group C receive traditional wound care: the primary outcomes were the wound surface area measurement, percentage of wound complete closure and percentage of days needed for surface area reduction before and after receiving the treatment protocol for two consecutive months, and the secondary outcomes were % of wound cause and location frequencies. Results The results showed a statistically significant reduction in wound surface area within groups A & B (P <0.05) while there was no statistically significant improvement of WSA in group C. Comparison between groups showed a statistically significant difference between mean values of WSA measured between study groups after treatment (p-value = 0.003) with lower values at group A & B in comparison to group C (p-values = 0.002 & 0.008 respectively) and no significant difference between group A & B (p-value = 0.361). Conclusion These findings suggest that group A is favored over group B in accelerating the wound-healing process of diabetic foot ulcers.